Impact of new-onset diabetes on clinical outcomes after ST segment-elevated myocardial infarction. (2nd November 2019) - Seo, Ji-Yeoun; Park, Jin-Sun; Seo, Kyoung-Woo; Yang, Hyoung-Mo; Lim, Hong-Seok; Choi, Byoung-Joo; Choi, So-Yeon; Yoon, Myeong-Ho; Hwang, Gyo-Seung; Tahk, Seung-Jea; Shin, Joon-Han
Abstract: Objective. Patients with diabetes have higher mortality rate than patients without diabetes after ST-segment elevated myocardial infarction (STEMI). Prognosis of patients with new onset diabetes (NOD) after STEMI remains unclear. The aim of this study was to evaluate the prognosis of patients with NOD compared to that of patients without NOD after STEMI. Design. This study was a retrospective observational study. We enrolled 901 STEMI patients. Patients were divided into diabetic and non-diabetic groups at index admission. Non-diabetic group was divided into NOD and non-NOD groups. Kaplan-Meier analysis and Cox's proportional hazard regression models were used to compare major adverse cardiac events (MACE) free survival rate and hazard ratio for MACE between NOD and non-NOD groups. Results. Mean follow-up period was 59 ± 28 months. Diabetes group had higher MACE than non-diabetes group ( p = .038). However, MACE was not different between NOD and non-NOD groups ( p = 1.000). After 1:2 propensity score matching, incidence of MACE was not different between the two groups. In Kaplan-Meier survival curves, MACE-free survival rates were not statistically different between NOD and non-NOD groups either ( p = .244). Adjusted hazard ratios of NOD for MACE, all-cause of death, recurrent myocardial infarction, and target vessel revascularization were 0.697 (95% confidence interval [CI]: 0.362–1.345, p = .282), 0.625 (95% CI: 0.179–2.183, p = .461), 0.794 (95% CI: 0.223–2.835, p = .723), and 0.506 (95% CI: 0.196–1.303, p = .158), respectively. Conclusion. This retrospective observational study with a limited statistical power did not show a different prognosis in patients with and without NOD.